Experiments in engagement: Designing public engagement with science and technology for capacity building. (August 2017) - Selin, Cynthia; Rawlings, Kelly Campbell; de Ridder-Vignone, Kathryn; Sadowski, Jathan; Altamirano Allende, Carlo; Gano, Gretchen; Davies, Sarah R.; Guston, David H.
Public engagement with science and technology is now widely used in science policy and communication. Touted as a means of enhancing democratic discussion of science and technology, analysis of public engagement with science and technology has shown that it is often weakly tied to scientific governance. In this article, we suggest that the notion of capacity building might be a way of reframing the democratic potential of public engagement with science and technology activities. Drawing on literatures from public policy and administration, we outline how public engagement with science and technology might build citizen capacity, before using the notion of capacity building to develop five principles for the design of public engagement with science and technology. We demonstrate the use of these principles through a discussion of the development and realization of the pilot for a large-scale public engagement with science and technology activity, the Futurescape City Tours, which was carried out in Arizona in 2012.